"Father, Forgive Them" (Luke 23:34a): Conflicting Interpretations and the Lucan Territory of Forgiveness - Szkredka, Sławomir (The catholic biblical quarterly, 2022)
, Interpretations of Luke 23:34a ("Father, forgive them, for they do not know what they are doing") are very diverse. I argue that this diversity is largely reflective of the difficulty inherent in articulating the workings of forgiveness. Both ancient classical and modern understandings of forgiveness are not easily applicable to Luke; and, vice versa, to our modern sense of forgiveness, Luke's text appears contradictory: Jesus's words of forgiveness, presumably canceling debt and forbearing retribution, seem to be negated by the fact of punishment visited upon Jerusalem and prophesied by Jesus. My argument will proceed in three stages: (1) surveying both the contemporary and the Greco-Roman forgiveness discourse; (2) summarizing the various strategies for negotiating the tension between forgiveness and punishment among the ancient and modern commentators on Luke 23:34a; and (3) situating forgiveness and punishment in Luke's own soteriological matrix, allowing for a more confident understanding of the Lucan notion of forgiveness.